University teaching in prison in the university penitentiary system of Sassari: practices, research and developments during the pandemic - Luisa Pandolfi; Emmanuele Farris (Formare, 2021)
This paper derives from the activities of the University Penitentiary Center of the University of Sassari and aims to explore the impact of the Covid 19 pandemic on university teaching in prison. The subject of penitentiary university teaching is innovative and relevant for educational research and brings into play different skills, professionals, services and institutions. The theoretical framework describes how the right to study in prison is declined on a methodological level. The field research carried out in Sardinia has tried to give the student's voice in prison and the point of view of educators on the educational and organizational impact on university study paths during the pandemic; it is a voice that returns the complexity of a difficult moment, but which also offers useful ideas and stimuli for a more aware restart of the limits and challenges to be faced, as well as good practices to be developed, particularly at the interface between different public institutions as the University and the Penitentiary Administration are.